Speech Perception and Information-Carrying Capacity for Hearing Aid Users of Different Ages - Hoppe, Ulrich; Hocke, Thomas; Mueller, Alexander; Hast, Anne (Audiology and Neuro-Otology, 2016)
Hearing impairment in the elderly is usually treated with conventional hearing aids; however, a large number of older people do not achieve sufficient speech recognition with hearing aids. The aim of the study was to describe speech perception with hearing aids in comparison to pure-tone hearing loss and maximum speech recognition scores for phonemically balanced words. Data from 392 hearing aid users with different degrees of hearing loss were evaluated retrospectively. In particular, pure-tone thresholds, the maximum monosyllabic word score, and the monosyllabic word score in quiet at conversational level with a hearing aid were analysed. The results showed that speech perception scores decline with increasing age. Even when corrected for pure-tone hearing loss, a significant decline in speech recognition scores after the age of 80 years was observed. Regarding the maximum monosyllabic word score, the effect is smaller but still observable; thus, speech recognition with hearing aids is significantly lower for older subjects. This can be attributed partially to the reduction of the information-carrying capacity in this group.
EVALuna2:33175